Association between obesity, overweight, elevated waist circumference, and insulin resistance markers among Brazilian adolescent students - Rodrigues, Rodolfo Rêgo Deusdará (2022)
(1) Background: There is still controversy concerning the most effective and efficient strategy to identify insulin resistance in adolescents. We estimated the level of fasting insulin (fasting insulin equivalent, FIeq) that would replicate the strength of the associations of obesity, overweight, and waist circumference with two insulin resistance markers: triglyceride/high-density lipoprotein (TG/HDL) and triglyceride/glucose (TyG); (2) Methods: We studied approximately 38,000 adolescents aged 12 to 17 years, sampled from a multicenter Brazilian school-based survey, The Study of Cardiovascular Risk Factors in Adolescents (Portuguese acronym, ERICA), conducted in 2013–2014. Fasting insulin equivalents for adiposity variables were calculated by dividing the beta coefficient of each adiposity measure by the fasting insulin beta coefficient from linear regression analysis according to age (12–14, 15–17 years old) and sex, and adjusted by smoking, alcohol consumption, physical inactivity, sedentary behavior, socioeconomic status, and Tanner stage; (3) Results: The FIeqs for obesity were greater than those for overweight and elevated waist circumference for both TG/HDL and TyG in early adolescence. The FIeqs for elevated WC were greater than those for obesity and overweight in adolescents aged 15 to 17 years; (4) Conclusions: Our study suggests that WC measurements might be useful to identify adolescents with insulin resistance, particularly in late adolescence.